Utilization And Application Of Research Findings In The Nigerian Public Sector – A Call For Change - Bello, Matthew Funsho; Mela, Keneth; Yakubu, Lydia (Universitas Airlangga, 2022)
Abstract Research outcomes or findings are regarded in developed nations as important in expanding existing knowledge on any phenomenon in the society. This is because it fosters growth of logical reasoning and it is crucial for socio-economic progress of the society. Findings from the study showed that the Nigerian government does not appreciate the importance of research outcomes or finding that is why the public sector is backward in terms of socio-economic development due to neglect of the research component in the economy; some of the importance of research findings include: The current status of research in the country is not encouraging to foster socio-economic development because Research and its findings as a tool for socio-economic development has not been properly put into use or applied appropriately; among the challenges besetting utilization and application of research findings are: lack of implementation of research findings, lack of reliable and valid data, secrecy and inadequate funding from both government and nongovernmental organizations. A content analysis and a descriptive research technique was employed for obtaining data through the use of secondary sources; e.g. reviewing of existing literature on the topic under investigation; the paper recommends that research should be adequately funded by the government with the support of the private sector, Research findings should be given priority and must be fully utilized and applied in policy formulation and implementation to achieve desired socio – economic growth and development and that: Research findings should be made available to the public for use in solving the human problems. Keywords: research findings, utilization, meaningful development and growth, content analysis, nigerian public sector Abstrak Hasil atau temuan penelitian di negara maju dianggap penting dalam memperluas pengetahuan yang ada tentang fenomena apa pun di masyarakat. Hal ini karena mendorong pertumbuhan penalaran logis dan sangat penting untuk kemajuan sosial ekonomi masyarakat. Temuan dari studi menunjukkan bahwa pemerintah Nigeria tidak menghargai pentingnya hasil penelitian atau temuan itu sebabnya sektor publik terbelakang dalam hal pembangunan sosial-ekonomi karena mengabaikan komponen penelitian dalam perekonomian; beberapa temuan penelitian yang penting antara lain: Status penelitian di tanah air saat ini tidak mendorong untuk mendorong pembangunan sosial-ekonomi karena Penelitian dan temuannya sebagai alat untuk pembangunan sosial-ekonomi belum dimanfaatkan atau diterapkan secara tepat; Di antara tantangan yang melanda pemanfaatan dan penerapan temuan penelitian adalah: kurangnya implementasi temuan penelitian, kurangnya data yang dapat diandalkan dan valid, kerahasiaan dan pendanaan yang tidak memadai baik dari pemerintah maupun lembaga swadaya masyarakat. Analisis isi dan teknik penelitian deskriptif digunakan untuk memperoleh data melalui penggunaan sumber-sumber sekunder; misalnya meninjau literatur yang ada tentang topik yang diselidiki; makalah ini merekomendasikan bahwa penelitian harus didanai secara memadai oleh pemerintah dengan dukungan sektor swasta, Temuan penelitian harus diprioritaskan dan harus dimanfaatkan dan diterapkan sepenuhnya dalam perumusan dan implementasi kebijakan untuk mencapai pertumbuhan dan pembangunan sosial-ekonomi yang diinginkan dan bahwa: Temuan penelitian harus tersedia untuk umum untuk digunakan dalam memecahkan masalah manusia. Kata kunci: temuan penelitian, pemanfaatan, perkembangan dan pertumbuhan yang berarti, analisis konten, sektor publik Nigeria